Success in the Digital Economy: Cloud Computing, SMEs and the impact to National Productivity - Fakieh, Bahjat; Blount, Yvette; Busch, Peter (ACIS, 2014)
The literature is scant around the take up rates of cloud computing by Small and Medium Enterprises (SMEs). This is important because Small and Medium Enterprises (SMEs) play a significant role in increasing national productivity. In Australia, SMEs employed around 70% of the total numbers of employees in 2011. This paper proposes a research program to examine how cloud computing can provide SMEs with the potential to achieve competitive advantage, increase efficiency and lift national productivity. The research will use both quantitative and qualitative measures to establish the take up rate of cloud computing and identify the critical success factors for SMEs when adopting cloud computing technologies.